Economic-Utilitarian and Spiritual-Existential Bases of Fostering Environmental Awareness in Mountain Dwellers - Moskalets, Viktor (Journal of Vasyl Stefanyk Precarpathian National University, 2014)
The article high lights the psychology economic-utilitarian motivation in mountain dwellers to care for nature as a basic resource in their recreation and relaxation activities – the main means of promoting the social and economic growth of mountain areas. Such motivation provides a psychological foundation for the spiritual-existential bases of ecological culture in mountain areas as well as in all natural climatic regions having recreation, relaxation, and health care potentials